Aetiopathology of rheumatoid arthritis - Taylor, PC; Kiriakidis, S (Elsevier, 2022)
Rheumatoid arthritis (RA) has a multifactorial aetiopathogenesis with both genetic and environmental factors implicated, giving rise to immune dysregulation with resultant joint inflammation and tissue damage. The emergence of biologic and small molecular targeted therapeutics has validated the role of many key molecules and cells in the pathogenesis of RA. In this article we update our previous review, adding any new developments within the last couple of years with regards to the major contributors to RA pathogenesis, including genetics, cellular components, cytokines and new potential signalling mechanisms and targets. Moreover, we update on any further evidence of the role of the microbiome in RA, and also new emerging concepts and challenges in RA therapy.